TPACK: a missing piece of the technology puzzle among special education (hearing impairment) teachers - Chong, Ai Peng; Mohd Daud, Shaffe (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The recent Malaysia’s educational blueprint had been put to focus on leveraging Information Communication Technology (ICT) to scale up high quality of learning across the country, special education is no exception. ICT integration in special education (hearing impairment) classroom is much more important due to the hearing impaired students who are generally classified as visual learners. However integrating ICT to the hearing impaired students could be more complicated because the disability of them are somehow invisible. Hence, 21st era special educators requires specific knowledge and skills to integrate ICT effectively in the hearing impairment classroom. Unfortunately, there was lacking theoretical frameworks for guiding the educational integration of technology in the past until the appearance of technological pedagogical content knowledge (TPACK) which conceptualized by Mishra & Koehler (2006). The introduction of TPACK model provides a conceptual lens to guide the teachers in designing and conducting technology-driven instruction. The idea stresses that effective ICT integration for a teaching subject matter not simply demands the knowledge of content, technology and pedagogy in isolation, but also of their inter-relationship with one another. This paper is a reference-based study in which information and data was assembled from the books, journal articles, conferences proceedings as well as thesis and dissertations. It seeks to provide an overview of the TPACK in the special education especially hearing impairment education. Moreover, it attempts to explore the factors influencing teachers' TPACK which hinder them from integrating technology in their teaching.